(3ebQC fGaY Hf YHOGdQMef GdeOfjs - (3eMeO Hf CMeO Hf jhSa Hf ehSi, CHh YHO Gddgs ((3ehSi Hf jhSa Hf ehSi Hf jhSa s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg Mb MeOgSCdfi ef jMH GdfXQ ai bQGAI CHj fYje fGaY Hf YHO GdQMef Cf CaQOgG dg Yf ZjQgG hCHjf dg ef CUhdgG eG jLH GdfXQ ajg hGdhbha Ydjg s
(3BNQgG (B:s
(3aGYde Pdc hJMbbg hQGY GdCUhd GdJi PcQfGgG , aYdjgG MaX LejY GdCUhd Je GdcJGH HYhf Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3JLhjO hbQGAGJ (B34) s
Keywords: (3GdbQGAGJ hGdJLhjOs